(untitled) (Experimental biology, 2025)
Currently, the impact of climate change on animals and plants on Earth is very great. In particular, this causes factors such as limitation, extinction, or an excessive increase in the number of living organisms, that is, an imbalance in the ecological system. In this regard, one of the main tasks is the systematic conduct of floristic and faunal studies in all regions of Kazakhstan. This article presents the results of research depending on the species composition, life form and ecology, and the frequency of occurrence of inhabited lichens in the pine forests of the Abai region located on the banks of the Irtysh River. The main purpose of the research work is the common pine (Pinus sulvestris L.) to consider their biological and ecological features with the identification of lichen species in certain areas of woodlands.